2015
DOI: 10.1080/15546128.2015.1049314
|View full text |Cite
|
Sign up to set email alerts
|

Teen Pregnancy Prevention Program Recommendations from Urban and Reservation Northern Plains American Indian Community Members

Abstract: Despite declines over the past few decades, the United States has one of the highest rates of teen pregnancy compared to other industrialized nations. American Indian youth have experienced higher rates of teen pregnancy compared to the overall population for decades. Although it's known that community and cultural adaptation enhance program effectiveness, few teen pregnancy prevention programs have published on recommendations for adapting these programs to address the specific needs of Northern Plains Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
0
16
0
3
Order By: Relevance
“…As it has been suggested that urban American Indian/Alaska Native youth tend to be more assimilated than reservation American Indian/Alaska Native youth to mainstream culture (McMahon, Hanson, Griese, & Kenyon, 2015), it may be the case that cultural/ethnic identity does not play a role in this particular sample with respect to attitudes towards and perceived impact of teen pregnancy. Few articles examine urban versus reservation American Indian/Alaska Natives and fewer still look at cultural identity and youth risky sexual behaviors.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As it has been suggested that urban American Indian/Alaska Native youth tend to be more assimilated than reservation American Indian/Alaska Native youth to mainstream culture (McMahon, Hanson, Griese, & Kenyon, 2015), it may be the case that cultural/ethnic identity does not play a role in this particular sample with respect to attitudes towards and perceived impact of teen pregnancy. Few articles examine urban versus reservation American Indian/Alaska Natives and fewer still look at cultural identity and youth risky sexual behaviors.…”
Section: Discussionmentioning
confidence: 88%
“…The Cohen’s kappa value was 0.62, “substantial” (0.61 to 0.80) when interpreted using the benchmarks set by Landis & Koch (1977). Additional validation techniques for the qualitative data were establishing through various means, including contingent validity through the use of diverse participant perspectives; descriptive validity through the use of verbatim responses; and interpretive validity through letting the themes of the study emerge directly from the data (McMahon, Hanson, Griese, & Kenyon, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Teen pregnancy rates for AI youth in this county are 109 per 1,000 (vs. 19.8 for White youth). The reservation site participants were relatively assimilated, with prior research indicating they reflected similarly on the sexual health and behaviors of their youth as did the urban site participants (Hanson, McMahon, Griese, & Kenyon, 2014; McMahon, Hanson, Griese, & Kenyon, 2015). The two different sites were included to provide an additional source of data triangulation.…”
Section: Methodsmentioning
confidence: 92%
“…Interviewees also focused on culturally and age‐appropriate communication techniques for working with AI/AN adolescent girls and their adult female caregivers. They recommended adapting the material to acknowledge the integral role of extended family in many Native communities, and to ensure that the information provides facts and does not usurp the familial role to provide values . Interviewees recommended not using directive language, which is supported by adolescent‐communication literature.…”
Section: Discussionmentioning
confidence: 99%